The Role of Teachers as Learning Managers in Enhancing Students’ Academic Achievement in Islamic Primary Education: A Perspective on Effective Learning Management - Mohammad Haqiqi; Badrul Mudarris (Universitas Nurul Jadid, 2025)
This study aims to describe, analyze, and evaluate the role of teachers as learning managers in improving students’ academic achievement in Islamic primary education. The background of this research is based on the phenomenon that the implementation of teachers’ roles as learning managers is still not optimal and varies among teachers, thereby affecting the quality of student learning outcomes. This study employs a descriptive qualitative approach with a case study design conducted at MI Darul Hikmah Al-Fatimiyah, Besuki, Situbondo, East Java, Indonesia. The research subjects include the principal, teachers, and students, with data collection techniques consisting of observation, in-depth interviews, and documentation. Data analysis was carried out through data reduction, data display, and conclusion drawing, supported by triangulation techniques to ensure data validity. The findings reveal that teachers have performed managerial learning functions, including planning, organizing, implementing, and evaluating instruction, although not yet consistently and innovatively. The main supporting factors include teachers’ commitment, students’ motivation, and principal leadership support, while the inhibiting factors include limited learning media, low integration of educational technology, and heterogeneous student abilities. The strategy applied is a student-need-based learning model through planning, implementation, and evaluation stages. The study also shows that the role of teachers as learning managers has a positive impact on improving students’ academic achievement. Therefore, strengthening teachers’ managerial competencies is essential for enhancing instructional quality and ensuring sustainable educational improvement in Islamic primary schools.